Continous Formative Assessment pada Pendekatan Hybrid Learning: Sebuah Study Evaluasi Persepsi - Asih Rohmani; Sri Winarno; M. Hafidz Ariansyah (Journal of Education and Teaching (JET), 2023)
Assessment is a crucial part of the learning process. In addition to assisting students in determining their level of comprehension and subject-matter mastery, assessment is an essential component of the learning process. Formative evaluation is now regarded as being at the forefront of the learning process. Formative assessment is a learning activity that tracks how well learners are acquiring competencies with the goal of obtaining maximum mastery. Consequently, Continuous Formative Assessment (CFA) is created as an alternative evaluation strategy that can be used to the educational process in the post-pandemic period, particularly in the setting of hybrid learning. The courses are split into two groups for this study's quasi-experimental methodology: the Control Group and the Experimental Group. While the Experimental Group uses CFA for evaluation, the Control Group uses formative-summative assessment. In terms of how students view CFA, data processing results show an average score of 3.35 and a standard deviation of 0.697. The highest average score, 3.78, shows that students can use CFA to achieve the desired learning results.